Early Mortality, Cardiovascular, and Renal Diseases in Women's Lives Following Hypertensive Disorders of Pregnancy: The Prospective Nationwide Study CONCEPTION - Grégory Lailler; Clémence Grave; Amélie Gabet; Pierre Joly; Nolwenn Regnault; Catherine Deneux‐Tharaux; Vassilis Tstsaris; Geneviève Plu‐Bureau; Sandrine Kretz; Jacques Blacher; Valérie Olie (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background We aimed to evaluate the impact of hypertensive disorders of pregnancy occurrence, recurrence, onset time, and severity on mortality and on a wide range of cardiovascular outcomes in France. Methods and Results CONCEPTION (Cohort of Cardiovascular Diseases in Pregnancy) is a French nationwide prospective cohort using data from the National Health Data System. We included all women in CONCEPTION with no history of a cardiovascular event who delivered in France for the first time between 2010 and 2018 (N=2 819 655). Hypertensive disorders of pregnancy and cardiovascular outcomes during the study follow‐up were identified using algorithms combining International Classification of Diseases, Tenth Revision (ICD‐10) coded diagnoses during hospitalization and purchases of medication between 2010 and 2021. We fitted Cox models with time‐varying exposure to assess the associations of hypertensive disorders of pregnancy with mortality and cardiovascular events. Women with gestational hypertension had a 1.25‐ to 2‐fold higher risk of stroke, acute coronary syndrome, peripheral arterial disease, pulmonary embolism, and chronic kidney disease, and a 2‐ to 4‐fold higher risk of rhythm and conduction disorder and heart failure. Women with preeclampsia had a 1.35‐ to 2‐fold higher risk of rhythm or conduction disorder and pulmonary embolism during follow‐up; a 2‐ to 4‐fold higher risk of stroke, acute coronary syndrome, and peripheral arterial disease; and a 7‐ to 9‐fold higher risk of heart failure and chronic kidney disease. They were 1.8 times more likely to die and 4.4 times more likely to die of cardiovascular causes. Conclusions Hypertensive disorders of pregnancy drastically increase the risk of mortality, cardiovascular, and renal events early after pregnancy. Recurrent, severe, and early‐onset preeclampsia further increases this risk.